2021
DOI: 10.1038/s41598-021-98771-6
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine and exercise provide comparable improvements to high fat diet-induced muscle dysfunction through enhancement of mitochondrial quality control

Abstract: Obesity induces skeletal muscle dysfunction. The pathogenesis of which appears to substantially involve mitochondrial dysfunction, arising from impaired quality control. Exercise is a major therapeutic strategy against muscle dysfunction. Trimetazidine, a partial inhibitor of lipid oxidation, has been proposed as a metabolic modulator for several cardiovascular pathologies. However, the effects of Trimetazidine on regulating skeletal muscle function are largely unknown. Our present study used cell culture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Skeletal muscle is an important target organ in IR. We found that TMZ, similar to exercise, had a beneficial effect on skeletal muscle in healthy and obese mice by enhancing MQC 14 22. Previous studies on patients with diabetic have shown that TMZ improves glucose usage as well as reduces glycemia and glycated hemoglobin with effects comparable to exercise 20 21.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Skeletal muscle is an important target organ in IR. We found that TMZ, similar to exercise, had a beneficial effect on skeletal muscle in healthy and obese mice by enhancing MQC 14 22. Previous studies on patients with diabetic have shown that TMZ improves glucose usage as well as reduces glycemia and glycated hemoglobin with effects comparable to exercise 20 21.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, Fragasso et al 40 found that in patients with systolic heart failure, TMZ treatment was associated with improved left ventricular function and regulated whole-body energy metabolism. In a previous study, we found that the body composition in HFD mice significantly improved following TMZ treatment, with increased muscle mass, decreased visceral fat, and a trend for a decrease in body weight 22. These findings suggested that TMZ may bring about beneficial effects on IR.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations